Many people in Scotland now benefit from anticipatory care before they die: an after death analysis and interviews with general practitioners. Issue 4 (13th April 2016) - Tapsfield, Julia; Hall, Charlie; Lunan, Carey; McCutcheon, Hazel; McLoughlin, Peter; Rhee, Joel; Leiva, Alfonso; Spiller, Juliet; Finucane, Anne; Murray, Scott A
Abstract : Background: Key Information Summaries (KIS) were introduced throughout Scotland in 2013 so that anticipatory care plans written by general practitioners (GPs) could be routinely shared electronically and updated in real time, between GPs and providers of unscheduled and secondary care. Aims: We aimed to describe the current reach of anticipatory and palliative care, and to explore GPs' views on using KIS. Methods: We studied the primary care records of all patients who died in 2014 in 9 diverse Lothian practices. We identified if anticipatory or palliative care had been started, and if so how many weeks before death and which aspects of care had been documented. We interviewed 10 GPs to understand barriers and facilitating factors. Results: Overall, 60% of patients were identified for a KIS, a median of 18 weeks before death. The numbers identified were highest for patients with cancer, with 75% identified compared with 66% of those dying with dementia/frailty and only 41% dying from organ failure. Patients were more likely to die outside hospital if they had a KIS. GPs identified professional, patient and societal challenges in identifying patients for palliative care, especially those with non-cancer diagnoses. Conclusions: GPs are identifying patients for anticipatory and palliative care more equitably across the different disease trajectories and earlier in the disease process than they were previously identifying patients specifically for palliative care. However, many patients still lack care planning, particularly those dying with organ failure.